7 Early experience with implantable LVAD at samsung medical centre, seoul. (9th April 2018) - Yang-Hyun, CHO
Abstract : The number of heart transplantation in Korea has been growing steadily. However, the waiting time for transplantation is also increasing. For 6 years, we have been implanting left ventricular assist devices (LVAD). Up to October 2017, 15 patients have had LVAD implanted at Samsung Medical Centre (see table 1). There were 5 bridge-to-candidacy patients and 10 destination therapy (DT) patients. Age range was 47 to 81 years. Six patients (40%) were on extracorporeal membrane oxygenation (ECMO) support and 4 were on dialysis preoperatively. Three patients required post-operative temporary right VAD support. There were no early (30 day) deaths, but 2 late deaths occurred. During the study period, LVAD were not covered by any Korean insurance system. At present, the role of LVAD is limited to bridge-to-candidacy or DT. However, in the near future, it may be utilised for purely bridge-to-transplantation.